(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to (play skills and their relationship to moral harassment in kindergarten children) as play is the child’s world full of fun, exploration and exploration, and for children, play represents life for them in every sense of it. The two researchers intended to build two measures, the first for playing and the second for moral harassment, and it was applied to a sample size of (400) children for the preliminary stage distributed in (50) governmental kindergartens for Nineveh Governorate, and the scale of play consisted of (63) items distributed into five areas: 1- Individual play and it consists of (12) items 2 - Group play consists of (15) items 3 - Parallel play 4 - Risk play 5 - Creative play, each one consists of (12) items, and the second scale included (40) items distributed into three areas, which are physical harassment and consisted of (20) items, verbal and mimic harassment consisting of (20) items, and the following statistical methods were used: The use of statistical programs: the statistical bag of the social sciences, the Pearson correlation coefficient, Alpha Cronbach coefficient, the retest method. The most prominent results are: That kindergarten children have various playing skills. In light of the results of the current research, a number of recommendations and proposals were reached.